The Effects of Strategic Alliances on Marketing Efforts: The Roles of Cooperation - Hsu, Tommy (Journal of Strategic Innovation and Sustainability, 2023)
Strategic alliances can be more commonly observed in today’s business practice even though the failure rate remains so high. In this paper, the definition of strategic alliances is formally documented; several different types of alliances are introduced; and reasons why so many firms have failed are discussed. Also, other than strategic alliances, a relatively newer notion, coopetition, is well defined and discussed as well. Finally, the author proposes a new model that intends to explain the relationship between strategic alliances and their effectiveness by introducing a potential moderator, coopetition. The author also provides research propositions for future further testing work and research.